Volume 6: Turbomachinery, Parts a and B 2006
DOI: 10.1115/gt2006-90547
|View full text |Cite
|
Sign up to set email alerts
|

On the Aerodynamics of Swept and Leaned Transonic Compressor Rotors

Abstract: ASME PAPER GT-2006-9054

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Interestingly they claimed that the highest efficiency gain was obtained with backward sweep and an optimized S-shaped camber line without losing a stall margin. That could support a finding of Benini and Biollo [5] where a backward-swept rotor had a higher efficiency and a larger choke flow than both the datum and a forward-swept design, posing against the general agreement on blade sweep. It can be assumed that when more blade design parameters are involved in transonic rotor design the current knowledge on blade lean and sweep only might need to change.…”
Section: Numerical Efforts Of Aerodynamic Re-design In a Single-stagementioning
confidence: 58%
See 1 more Smart Citation
“…Interestingly they claimed that the highest efficiency gain was obtained with backward sweep and an optimized S-shaped camber line without losing a stall margin. That could support a finding of Benini and Biollo [5] where a backward-swept rotor had a higher efficiency and a larger choke flow than both the datum and a forward-swept design, posing against the general agreement on blade sweep. It can be assumed that when more blade design parameters are involved in transonic rotor design the current knowledge on blade lean and sweep only might need to change.…”
Section: Numerical Efforts Of Aerodynamic Re-design In a Single-stagementioning
confidence: 58%
“…However, their modified blades did not represent the best that could be produced for the applied lean (and/or sweep) because of no changes at each blade section. Benini and Biollo [5] numerically investigated the impact of axially-swept and tangentially-leaned shapes on the NASA Rotor 37 datum, and confirmed that a positively-leaned rotor had a substantial increment of efficiency and a reduction of shock strength. As mentioned in their paper, no attempts were made to change other blade design parameters like camber, supposing findings cannot be generalized.…”
Section: Numerical Efforts Of Aerodynamic Re-design In a Single-stagementioning
confidence: 82%
“…As mentioned in [16,17], it is weakening the passage's shock and it is reducing loss core near the tip of the suction surface. A recent numerical work gave a point of view on the impact of blade curvature in transonic compressor rotors, showing how the movement of blade sections in the tangential direction can influence the internal flow field [18,19]. Another research group investigated the aerodynamic effects induced by several tangential blade curvatures on the same rotor.…”
Section: Mixing Between Blade-to-blade Plane Group and Hub-to-shroud mentioning
confidence: 99%
“…Generally, active flow control methods mainly include aspiration/suction techniques, tip injection (Taghavi-Zenouz et al, 2018), plasma actuator (Akcayoz et al, 2016) and acoustic excitation (Yarusevych et al, 2005). The latter is mainly composed of sweep and dihedral (Copenhaver et al, 1996;Benini et al, 2007), casing treatment (Mao et al, 2018a;2018c), blade tip winglet (Zhong et al, 2013;Jung et al, 2018), vortex generators (Hergt et al, 2012) and non-axisymmetric endwall (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%